ДЕНЕДЕН ТЫС ҰРЫҚТАНДЫРУ БАҒДАРЛАМАСЫНДА АНЕУПЛОИДТЫ АБЕРРАЦИЯЛАРДЫ АНЫҚТАУ (Experimental biology, 2009)
During carrying out FISH-diagnostics has been established dependence of frequency occurrence aneuploidies from some physiological factors, and also has been shown, that the reproductive anamnesis ofthe woman can influence their occurrence.
Keywords: FISH-diagnostic